2021
DOI: 10.48550/arxiv.2101.07481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Density-Ratio Based Personalised Ranking from Implicit Feedback

Abstract: Learning from implicit user feedback is challenging as we can only observe positive samples but never access negative ones. Most conventional methods cope with this issue by adopting a pairwise ranking approach with negative sampling. However, the pairwise ranking approach has a severe disadvantage in the convergence time owing to the quadratically increasing computational cost with respect to the sample size; it is problematic, particularly for largescale datasets and complex models such as neural networks. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In contrast to the CPE approach that estimates 𝑝 (𝑦 = +1|𝑒, 𝑖) = 𝑝 (𝑖 |𝑒, 𝑦 = +1)𝑝 (𝑦 = +1|𝑒)/𝑝 (𝑖 |𝑒), the recently-proposed density ratio estimation (DRE) approach [57] directly estimates the density ratio 𝑝 (𝑖 |𝑒, 𝑦 = +1)/𝑝 (𝑖 |𝑒) through the minimisation of the Bregman divergences [55], which can be empirically approximated with positive-unlabelled data. As the main distinction of the DRE approach from its CPE counterpart, the ranker model in the DRE approach does not need to estimate class prior 𝑝 (𝑦 = +1|𝑒) (i.e.…”
Section: Paradigms Of Personalised Rankingmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast to the CPE approach that estimates 𝑝 (𝑦 = +1|𝑒, 𝑖) = 𝑝 (𝑖 |𝑒, 𝑦 = +1)𝑝 (𝑦 = +1|𝑒)/𝑝 (𝑖 |𝑒), the recently-proposed density ratio estimation (DRE) approach [57] directly estimates the density ratio 𝑝 (𝑖 |𝑒, 𝑦 = +1)/𝑝 (𝑖 |𝑒) through the minimisation of the Bregman divergences [55], which can be empirically approximated with positive-unlabelled data. As the main distinction of the DRE approach from its CPE counterpart, the ranker model in the DRE approach does not need to estimate class prior 𝑝 (𝑦 = +1|𝑒) (i.e.…”
Section: Paradigms Of Personalised Rankingmentioning
confidence: 99%
“…user's activity), which is a constant value and does not affect the predicted ranking for 𝑒; thus, it avoids the estimation error of 𝑝 (𝑦 = +1|𝑒) in the ranker model. Several studies [45,57] have shown that the advantage of the DRE-based loss functions for top-𝐾 ranking problems by weighing the items in the top of ranked lists in contrast to the CPE approach. Togashi et al [57] empirically demonstrated the advantage of the DRE-based approach in terms of efficiency and effectiveness for top-𝐾 personalised recommendation.…”
Section: Paradigms Of Personalised Rankingmentioning
confidence: 99%
See 3 more Smart Citations